Báo cáo trường hợp bệnh nhân đa u tuỷ xương được ghép tế bào gốc tạo máu tự thân tại BVTW Huế - Hiếu, Đặng Trần Hữu; Thăng, Nguyễn Duy; Trí, Tôn Thất Minh; Tránh, Nguyễn Văn; Yến, Phùng Thị Hoàng; Hiếu, Võ Thế; Hải, Lê Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
A